Pochodzenie i upadek człowieka w "Traktatach wielkanocnych" św. Gaudentego z Brescii - Degórski, Bazyli (Vox Patrum, 2013)
The article surveys the teaching of Gaudentius on anthropology and especially on the Creation of human being and his primordial fall. The doctrine of St. Gaudentius recalls that of the Fathers, since he was depending on them and at the same time he had an influence on their works, so he can be inserted in a theological sequence: Origen (ca. 185-254), Basil of Caesarea (329-379), Gregory of Nyssa (335-395), Ambrose (339-397), Evagrius Ponticus (345-399), Philastrius (died ca. 397), Gaudentius (died 410), Augustine of Hippo (354-430), John Cassian (360-435), Quodvultdeus (died 454). The anthropological teaching of St. Gaudentius is an essential part of the wider Patristic Tradition, from which he takes exegetical elements, while at the same time providing many original insights.